MENDESAIN KOMPUTER SEBAGAI MEDIA ALTERNATIF BELAJAR MANDIRI - Hardianto, Deni (MAJALAH ILMIAH PEMBELAJARAN, 2007)
AbstractThe most important thing in learning process is the interaction between teacher and learner. This interaction creates knowledge transfer. Knowledge transfer is created in various modes and methods, and can be achieved through learning media. There are some failures in learning That is caused by obstacles in the interaction between teacher and learner. These obstacles are physiological, psychological, cultural and environmental.One of the solutions of this problem is to use computer as an interactive media. This is expected to stimulate brain, mind, attention and interest of the learner that learning can occur.Using computer as an independent learning media must consider instructional rules.Keywords : computer, media, independent learning